Tecnologias digitais e pandemia: o ensino remoto emergencial em uma escola do alto sertão sergipano - Alves, Erinaldo (2023)
The main objective of this research is to analyze the implications of the insertion of digital technologies in the performance of teachers in a school in the upper hinterland of Sergipe, during emergency remote teaching, in the period of the COVID-19 Pandemic. It also presents as secondary objectives to identify the technological interfaces used by teachers during emergency remote teaching, to relate the difficulties experienced by teachers in the use of technologies for classes during the ERE, in addition to analyzing the symmetries and dissimilarities between the guidelines published by the Secretary of State of Education and Culture and the work developed by teachers. In this sense, the study was justified both by personal motivations, linked to academic training and my professional career, by the need to understand how teachers developed classes, what were the implications of using technologies, what technological interfaces were used by teachers and the difficulties in using such resources, as well as the social relevance it presents. The research is qualitative in terms of approach, using the case study as a method. It was carried out in a school in Alto Sertão Sergipano and used a semi-structured interview as a data collection technique, applied with eight teachers from the school which I named Colégio Galileu Galilei to preserve its identity. Data analysis was carried out from the perspective of teaching research by Freeman (1998) and the coding process by Auerbach and Silverstein (2003). The results showed how teachers acted during emergency remote teaching and what were the implications of using technologies in remote classes. Data analysis revealed WhatsApp and Google Meet themes as the main devices for remote classes; Lack of training in digital technologies: challenges for the development of remote classes; Limits and perspectives of teachers' performance in remote teaching; Teachers' challenges and difficulties during the ERE; The use of digital technologies at school before the pandemic; Learning assessment in the context of ERE; Learning deficits during ERE: a problem to be faced; The health of teachers in the pandemic period and the relationship with the ERE and, Law nº 8.847/2021: purpose and relationship with the ERE.